Pengaruh Jarak Tray Aerasi Terhadap Penurunan Kadar Besi (Fe) Air Sumur Bor - Serlya Ulfa; Sulaiman Hamzani; Muhammad Irfa'i (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2019)
Abstract: Distance of Aerated Tray and Length of Deposition Time in Reducing Iron (Fe) Level in Drilled Well Water. Well bore wijaya street 7 Kelurahan Sungai Paring, Kecamatan Martapura, physically looks yellowish and slightly tasted. Based on the preliminary test of iron content of 3.50 mg / L and pH 4 compared to Republic of Indonesia Minister of Health Regulation No. 32 of 2017, has not met the requirements, namely iron 1.0 mg / L and pH 6.5-8.5. The purpose of this study is to find out the magnitude of the effect of the distance of aeration Tray on decreasing the iron content of borehole water and pH on borehole water. Type of experimental research with Pretest-Postest Without Control Group. The population in this study was all water in the wellbore. The sample of this research is borehole water. Analysis of the effect of variations in height and duration of settling using the Two Way Anova test shows sig. (0.000)